2014
DOI: 10.1007/s10561-014-9436-y
|View full text |Cite
|
Sign up to set email alerts
|

The use of autologous fibrin as a scaffold for cultivating autologous conjunctiva in the treatment of conjunctival defect

Abstract: The purpose of this study was to compare the use of autologous fibrin to human amniotic membrane (HAM) as a scaffold in cultivating autologous conjunctiva for transplantation in treatment of conjunctival defect. An experimental study was performed using 18 adult New Zealand white strain rabbits which were divided into 3 groups. Each group consists of 6 rabbits. The conjunctiva on the temporal site was excised to create a conjunctival epithelial defect. The excised area in the Group 1 was transplanted with auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Studies supporting goblet cell repopulation on AM have been mostly conducted through cultivation of conjunctival epithelial cells on AM. Additionally, most of the studies have not reported the percentage of goblet cells [34,65,66]. Three in vivo studies on rabbits have also reported goblet cell repopulation after implantation of cryopreserved AM for conjunctival reconstruction, but none have reported the number of cells [10,65,67].…”
Section: Discussionmentioning
confidence: 99%
“…Studies supporting goblet cell repopulation on AM have been mostly conducted through cultivation of conjunctival epithelial cells on AM. Additionally, most of the studies have not reported the percentage of goblet cells [34,65,66]. Three in vivo studies on rabbits have also reported goblet cell repopulation after implantation of cryopreserved AM for conjunctival reconstruction, but none have reported the number of cells [10,65,67].…”
Section: Discussionmentioning
confidence: 99%
“…It is biocompatible, degradable, and promotes cell adhesion, which makes it an excellent material for tissue engineering [ 32 ]. It has been used as a scaffold to engineer dermis [ 33 ], cornea [ 34 , 35 ], and even rabbit conjunctiva [ 18 ]. Based on the success of these studies, we have used fibrin to develop the new three-dimensional model described here.…”
Section: Discussionmentioning
confidence: 99%
“…By following the principles of tissue engineering, a conjunctival equivalent with a multilayered stratified epithelium and individual interspersed goblet cells can be developed in vitro by cultivating conjunctival explants on a matrix that has supportive niche features to facilitate adhesion, proliferation, as well as differentiation of epithelial and goblet cells under defined conditions. Various biomaterials for direct conjunctival replacement, as mentioned above, ranging from decellularized matrixes to artificial synthetic polymers, could possibly be adapted for conjunctival equivalent engineering, such as decellularized amniotic membranes, 32 , 130 decellularized porcine conjunctiva, 17 decellularized porcine pericardium, 10 fibrin, 131 , 132 collagen, 112 , 113 PLGA, 133 PCL, 118 , 134 polyester, 133 and 3D‐printed membranes based on a blend of previously described biomaterials. 81 These biomaterials act as carrier scaffolds of epithelial cells during in vitro culture.…”
Section: Cellular Approachesmentioning
confidence: 99%